Familial hypercholesterolaemia: a global call to arms - Vallejo-Vaz, A.J. (2015)
Familial Hypercholesterolaemia (FH) is the commonest autosomal co-dominantly inherited condition affecting man. It is caused by mutation in one of three genes, encoding the low-density lipoprotein (LDL) receptor, or the gene for apolipoprotein B (which is the major protein component of the LDL particle), or in the gene coding for PCSK9 (which is involved in the degradation of the LDLreceptor during its cellular recycling). These mutations result in impaired LDL metabolism, leading to life-long elevations in LDLcholesterol (LDL-C) and development of premature atherosclerotic cardiovascular disease (ASCVD) [1e3]. If left untreated, the relative risk of premature coronary artery disease is significantly higher in heterozygous patients than unaffected individuals, with most untreated homozygotes developing ASCVD before the age of 20 and generally not surviving past 30 years [2e5]. Although early detection and treatment with statins and other LDL-C lowering therapies can improve survival, FH remains widely underdiagnosed and undertreated, thereby representing a major global public health challenge.